(3eLGeY GdMbGFbs - (3GdMSjfj, GdNGOej, GdfbTHfOj, GdMfaj, CHh SYjO, eMeO Hf eUWai Hf YKeGf, J (B1176 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO QH GdYGdejf hHYO agPg eLGeY GdMbGFb hGdbhGYO LhGeY GdQhGFb hGdahGFO ef GdCUhd cGajI aj GdhUhd GdTQYjI HGdJeGSGJ GdENhGfs
(3BNQgG (B:s
(3dG jfJYH CMO eVeG Yf CMO HdG fjGHI hhcGdI hhdGjI dG jYJeO Ydi GdMX hdG jYed Hg dG jSeY GdOYhi HYO GdEHQGA GdYGe EdG HMb MGOK dGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 68s
(3eYLe GdeDdajf (B3 / 692s
(3EjVGM Gdecfhf (B2 / 430s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3CUhd Gdabgs